Semiotic Analysis of Roland Barthes on Da'wah Content of Ustadzah Halimah Alaydrus Through YouTube Channel - Tamamiyah, Lutfiyatut (Islamic Journal of Communication and Public Discourse, 2025)
Backround: This research examines the semiotic construction of meaning in digital Islamic da'wah content through analysis of Ustadzah Halimah Alaydrus's YouTube channel using Roland Barthes' three-level framework of denotation, connotation, and myth.Objective: As female Islamic preachers increasingly utilize digital platforms to disseminate religious teachings, understanding how meaning is semiotically constructed becomes critical for comprehending contemporary religious communication.Method: This qualitative study employs semiotic content analysis on eight selected videos representing diverse themes and high audience engagement.Findings and Implications: At the denotative level, findings reveal consistent formal presentation through text-based visuals, voice-only audio, and structured discourse creating distinctive brand identity. Connotative analysis demonstrates how these elements activate cultural codes related to Islamic piety, feminine virtue, and religious authenticity, negotiating tensions between tradition and modernity through sophisticated symbolic communication. Mythological analysis uncovers how content naturalizes the "Pious Femininity Synthesis"—presenting conservative Islamic gender norms and contemporary women's aspirations as perfectly compatible—while constructing "maternal wisdom authority" through epistemological, genealogical, experiential, pedagogical, and moral positioning mechanisms.Conclusion: Findings contribute theoretically by demonstrating Barthesian semiotics' effectiveness for religious discourse analysis, practically by revealing semiotic strategies for digital da'wah effectiveness, and critically by exposing ideological dimensions wherein female religious voice expansion coexists with naturalization of conservative gender hierarchies. The study provides comprehensive understanding of how digital Islamic content shapes contemporary religious identity and consciousness through layered meaning construction, offering insights valuable for preachers, religious institutions, media literacy educators, and scholars of digital religion.